Development and validation of a questionaire as a screening tool for developmental disability in 9 month old infants : September 1996 - January 1997 - Wicht, Carl Bryce (Department of Paediatrics and Child Health, 2018)
In the past two decades major focus has been placed on child's rights, survival and development. This has occurred both on an international level and, since the inception of the Government of National Unity (GNU) in South Africa, nationally, provincially and locally through various development programmes. Development in a child concerns the sequential acquisition of cognitive, motor and social skills. Adverse biological and environmental factors will have a major negative impact on a child's development. It is therefore crucial that children affected by these adverse factors are identified as early as possible, to prevent disability or facilitate intervention to ensure that they reach their maximum developmental potential. The global prevalence for developmental disability (DD) is 7-10% of the population. The national prevalence for South African children is not known but a recent Disability Survey by the Department of Health in 1998 quotes 5. 7% - 6.1 % for the overall population. Developmental disability is therefore an important priority to be addressed, especially at the primary health care level. This has been highlighted in the White Paper on Integrated National Disability Strategy of the GNU in 1997. The efficacy of intervention for developmental disabilities is debated. Scientifically this efficacy has not been proven unequivocally but there is consensus from parents, professionals and advocacy groups that early intervention is beneficial. Taken that early identification is essential, screening is the ideal method in the South African context for detection of developmental disability. There are numerous screening tools used for this purpose which need to fulfil certain criteria to ensure effectiveness. Important issues around existing developmental screening tools have been: time taken to administer the test; reliability, validity and sensitivity; measurement methods; ease of administering; and applicable age range. Questions which record parents' or caregivers' observations of their child's developmental skills have been used as effective screening tools for developmental disability. A large study which assessed prevalence of disability using a "Ten Question" format has been used extensively in Bangladesh and found to be effective. A 10-question tool was developed to screen for developmental disabilities in 9-month-old infants, the age of attendance at clinics for measles immunisation. The questions focused on the four areas traditionally tested in developmental assessments, namely speech and hearing, gross and fine motor, vision and personal/social functions. Other factors such as weight, head circumference, dysmorphic features and chronic illness were documented concurrently. The 9-month screening tool in this study was tested at Site B Clinic (Khayelitsha) and Eastridge Clinic (Mitchells Plain) and extended to high risk clinics such as the Neonatal Elevated Risk, Cerebral Palsy and Developmental Clinics of Red Cross War Memorial Children's Hospital. This was a prospective observational study. 235 9-month-old infants were seen between the period September 1996 to January 1997. The interviews were conducted in Xhosa (53%), Afrikaans (28%) and English (19%). The questionnaire was administered to the parent or caregiver of each infant. This was followed by an examination and neurodevelopmental assessment of the infant. On assessment 192 infants (82%) had no disability, 39 (16%) had developmental disability and 4 (2%) were at risk for motor disability. A further analysis of the 39 infants with developmental disability revealed that 25 (64%) were language impaired only, 2 (5%) were motor disabled and 12 (31%) were globally disabled (i.e. in both language and motor areas). Males and females were equally affected. The results showed that the 9-month screening questionnaire is a valid tool for the screening for developmental disability. The overall sensitivity of the questionnaire was 97.7% (95% Confidence interval [CI] of 95.8 - 99.6) and specificity 88.5% (95% CI of 84.4 - 92.6). The positive predictive value was 65.6% and negative predictive value 99.4%. Only one infant who was at risk for motor disability was missed by the questionnaire. On evaluation of the questions in specific areas (i.e. speech, hearing, motor, vision, squint), the numbers assessed were too small for meaningful analysis. As personal and social development involves motor, language and hearing skills, this area was not used on its own in the overall assessment of the infant, but those questions were incorporated into other areas of the screen. Of concern was that a number of infants screened positive for DD on certain questions (e.g. language), but on assessment were found to have disability i n a different developmental area (e.g. motor). In these cases, the questionnaire identified the children with disability - but for the incorrect reason. Certain issues would need to be addressed prior to implementation of the screening tool to ensure an adequate, appropriate screening procedure and prevention of falsely raising the expectations of parents. This involves personnel training, monitoring of screening, referral mechanisms, intervention once DD is identified and involvement of the family as a partner in the process.